Media self-regulation through media literacy insights from the Cebu Citizens-Press Council (CCPC) - Quintana, Ma. Theresa Angelina S.; Arao, Danilo Araña; University of the Philippines Diliman. College of Mass Communication
Abstract: This study analyzed how the Cebu Citizens-Press Council (CCPC) promotes self- regulation among the Cebu press and media literacy with the Cebu public. Set against a synthesized framework of media self-regulation that incorporates the theories of social responsibility (Hutchins Commission, 1942), new media monopoly (Bagdikian, 2004), public sphere (Habermas, 2006) and network society (Castells, 2010), the researcher studied documents and analyzed the interviews of key informants to answer these objectives: 1) history of the CCPC in the context of media self-regulation initiated by the community press in Cebu; 2) handling by Cebu newspapers and the CCPC of citizens? complaints about accuracy and fairness or right of reply in local newspapers; 3) CCPC campaigns to promote media self-regulation with the Cebu media and the public; 4) CCPC campaigns to promote media literacy among citizens and Netizens; and 5) assessment of the CCPC?s promotion of media self-regulation and media literacy through its reactive and pro-active mechanisms. Media self-regulation thrives in a setting that involves the stakeholdership of four key sectors: newspapers, media advocacy groups, citizens and Netizens. Media self-regulation can be enhanced, balanced and sustained through media literacy, which ensures greater participation of citizens and Netizens as media watchdogs and defenders of freedom of expression.
Vita.
Thesis (Master of Arts in Journalism) -- University of the Philippines Diliman
Keywords: Mass media policy -- Philippines; Mass media -- Law and legislation -- Philippines